Impaired sperm maturation in conditional Lcn6 knockout mice†. Issue 1 (13th October 2017) - Yin, Qianqian; Shen, Jia; Wan, Xiaofeng; Liu, Qiang; Zhou, Yuchuan; Zhang, Yonglian
Abstract: Human LCN6, a lipocalin protein, exhibits predominant expression in epididymis and location on the sperm surface. However, the biological function of LCN6 in vivo remains unknown. Herein, we found that unlike human LCN6, mouse Lcn6 gene encoded two transcript variants that were both upregulated by androgen. Subsequently, we generated a conditional knockout mouse model to disrupt Lcn6 in the adult and investigate its function. In this model, spermatogenesis was normal and Lcn6 deficiency did not affect the natural birth rate of male mice or in vitro fertilization ability of their cauda epididymal sperm. Nevertheless, sperm from the cauda epididymis of the Lcn6 null mice underwent a sustained increase of acrosome reaction frequency whether capacitated or not ( P < 0.01). Consistent with premature acrosome reaction, sperm from knockout mice had significantly increased intracellular calcium content when extracellular calcium was supplied ( P < 0.01). These results demonstrate an important function of LCN6 in preventing calcium overload and premature acrosome reaction of sperm and suggest a potential risk factor of LCN6 deficiency for sperm maturation. Summary Sentence: The mouse ortholog of human LCN6, of which two transcript variants exhibit specific expression in caput epididymis and positive regulation by androgen, is involved in preventing calcium overload and premature acrosome reaction of sperm.